Peripheral and central processes in hearing - JORASZ, U.; MOORE, B.C. J. (Archives of Acoustics, 2000)
One of the important problem in contemporary psychoacoustics is what can be instrumental in eliminating a relatively wide gap between peripheral — within-channel — and central — across-channel — auditory processes. The authors argued that CMR and MDI — two forms of auditory masking — can be useful in clarifying this problem. The mechanisms involved in the both effects are peripheral and central as well.